Medullary thymic epithelial stem cells: role in thymic epithelial cell maintenance and thymic involution. Issue 1 (May 2016) - Hamazaki, Yoko; Sekai, Miho; Minato, Nagahiro
Summary: The thymus consists of two distinct anatomical regions, the cortex and the medulla; medullary thymic epithelial cells (mTECs) play a crucial role in establishing central T‐cell tolerance for self‐antigens. Although the understanding of mTEC development in thymic organogenesis as well as the regulation of their differentiation and maturation has improved, the mechanisms of postnatal maintenance remain poorly understood. This issue has a central importance in immune homeostasis and physiological thymic involution as well as autoimmune disorders in various clinicopathological settings. Recently, several reports have demonstrated the existence of TEC stem or progenitor cells in the postnatal thymus, which are either bipotent or unipotent. We identified stem cells specified for mTEC‐lineage that are generated in the thymic ontogeny and may sustain mTEC regeneration and lifelong central T‐cell self‐tolerance. This finding suggested that the thymic medulla is maintained autonomously by its own stem cells. Although several issues, including the relationship with other putative TEC stem/progenitors, remain unclear, further examination of mTEC stem cells (mTECSCs) and their regulatory mechanisms may contribute to the understanding of postnatal immune homeostasis. Possible relationships between decline of mTECSC activity and early thymic involution as well as various autoimmune disorders are discussed.